ORIENTASI SUDUT LILITAN BENANG KATUN TERHADAP KEKUATAN TARIK PADA PIPA KOMPOSIT FILAMENT WINDING - Ardian Dwi Saputra; M. Fahrur Rozy H; Agus Triono; Imam Sholahuddin (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Cotton fibers currently use in many industries textiles, easy gotten in the market, and a cheap price. Using of fiber would be able to solve the environtment problems, reduce the metal using, particularly in the oil and gas industries. In this study, composite pipes are made by cotton fibers as reinforcement, particles of montmorillonite as filler, and unsaturated polyester as matrix. From that consideration this study was conducted to obtain that analysis of tensile strength composite cotton fibers. With the pattern of variation woven fiber direction angle towards the corner fibers 450, 550, 650, 750, and 850. From the test results the highest tensile strength values is obtained by a composite pipe with fiber direction angle of 850. The test results showed that the tensile strength of the cotton fiber reinforced composite pipe with direction of 450 angle fiber is 3.76 MPa, for direction of 550 angle fiber tensile strength is 1.28 MPa, for direction of 650 angle fiber tensile strength is 10.691 Mpa, for direction of 750 angle fiber tensile strength is 14.465 Mpa, and for direction of 850 angle fiber tensile strength 28.617 MPa. Keywords: Cotton fiber, unsaturated polyester, filament winding method, montmorillonite, Tensile Strength